Effect of Doping of Transition Metals Over Titania Based Nanocatalysts on the Degradation of Harmful Insecticides - Amala Infant Joice, J.; Ramya, G.; Vaithiyanathan, R.; Ramakrishnan, R.; Sivakumar, T. (Asian Journal of Chemistry, 2012)
Insecticides, pesticides and herbicides pollute the ground water to the larger extent. Their degradation by conventional methods do not lead to complete mineralization. Photodegradation using semi conductor oxides to remove these pollutants completely from water. TiO2, SrTiO3, Ni/Ru-TiO2 and Ni/Ru-SrTiO3 were prepared by sol-gel method and characterized by XRD, UV-DRS and BET surface area measurements. In the photodegradation of two important widely used insecticides such as thiamethoxam and acetamiprid has been studied using bare and metal supported TiO2 and SrTiO3 photocatalysts. It was observed that doping of transition metals Ni and Ru over TiO2 and SrTiO3 increased the degradation efficiency. All the catalysts degraded both but to different extents. Among them Ru doped catalysts degraded the insecticides in a very short time when compared to the time taken by other catalysts. Total organic carbon analysis was also carried out to study the extent of mineralization and the results showed that all the catalysts mineralized both the insecticides significantly.